THE EFFECT OF COMPETENCY, MOTIVATION, AND ORGANIZATIONAL CULTURE ON THE EMPLOYEE PERFORMANCE AT THE JAYAKARTA HOTEL, BANDUNG, INDONESIA - Suryana H. Achmad (Institut Pariwisata dan Bisnis Internasional, 2016)
Human resources in a company is an asset that can realize the achievement of the company’s mission to obtain benefits. The Jayakarta Bandung Hotel has 90% of employees who are competent and certified, but there are still complaints about the services provided. Therefore, this study was done to determine the influence of competence on performance, motivation on performance, and organizational culture on performance; and the influence of the competence, motivation, and work culture on the employee performance. This study used a quantitative research method approach with descriptive statistics, the data collection tool of questionnaires. The population was all employees of The Jayakarta Bandung Hotel with a purposive sample of 66 employees. The results showed that: employees’ competence tended to be at a sufficient value (a significant effect on the performance); employees’ motivation tended to be at a good value (a significant effect on the performance); and work culture tendency tended to be at a sufficient value to affect the performance. In conclusion, statistical hypotheses were accepted, indicating direct influence of X1 on Y was 9.61%. The value of indirect effect of X1 through X2 on Y was 9.85%, and that of X1 through X3 on Y was 5.39%. The total effect of X1 was 24.80%.